A simple constant switching frequency of direct torque control of brushless DC motor - Yusnida Ahmad Tarmizi; Auzani Jidin; Kasrul Abdul Karim; T. Sutikno (Institute of Advanced Engineering and Science, 2019)
This paper discusses about direct torque control of Brushless DC motor by injecting the triangular waveform and using PI controller in order to reduce the torque and obtain constant switching frequency. Brushless DC motor are widely used in applications which require wide range of speed and torque control because of robust, longer lifespan, faster torque response and able to operate at high speed. Unlike conventional three phase DTC of induction machine (IM),the proposed DTC approach introduces two phase conduction mode. Besides that, the magnitude flux is considered constant in which the results only gains from constant torque region. Thus, the flux control loop is eliminated while implement this scheme. Using the triangular waveform that will be compare with actual torque, the proper switching pattern can be selected to control the generated torque and reducing commutation torque ripple. The torque response depends on the speed of the stator flux linkage which is directly controlled by selecting appropriate voltage space vectors from a look-up table to make sure the torque error within the band. The validity of the proposed control scheme for constant switching frequency and reduce torque ripple are verified through simulation and experimental results.